2012
DOI: 10.1021/ma300910m
|View full text |Cite
|
Sign up to set email alerts
|

Melt and Solid-State Structures of Polydisperse Polyolefin Multiblock Copolymers

Abstract: Crystallization in polydisperse ethylene–octene multiblock copolymers, polymerized via chain shuttling chemistry, is examined using two-dimensional synchrotron small- and wide-angle X-ray scattering on flow-aligned specimens. The multiblocks are composed of alternating crystalline (hard) blocks of low 1-octene content and amorphous (soft) blocks of high 1-octene content; the block lengths and the number of blocks per chain are characterized by most-probable distributions. These polymers self-assemble into lame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
159
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(165 citation statements)
references
References 50 publications
6
159
0
Order By: Relevance
“…Concerning possible future applications of DPD to studying the phase behavior of block copolymers we would like to mention, first of all, Markovian (random correlated) multiblock copolymers, a model that was deeply studied in theory since the seminal paper by Milner, Fredrickson, and Leibler 79 and recently attracted the attention of experimentalists [80][81][82] due to the progress in the controlled synthesis of multiblock polyolefins. 83 Comprehensive simulation techniques 84 reveal only short-range order in the disordered phase (microemulsion), which, however, possesses interesting mechanical characteristics, and it would be interesting to search for long-range ordered structures with the help of DPD.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning possible future applications of DPD to studying the phase behavior of block copolymers we would like to mention, first of all, Markovian (random correlated) multiblock copolymers, a model that was deeply studied in theory since the seminal paper by Milner, Fredrickson, and Leibler 79 and recently attracted the attention of experimentalists [80][81][82] due to the progress in the controlled synthesis of multiblock polyolefins. 83 Comprehensive simulation techniques 84 reveal only short-range order in the disordered phase (microemulsion), which, however, possesses interesting mechanical characteristics, and it would be interesting to search for long-range ordered structures with the help of DPD.…”
Section: Discussionmentioning
confidence: 99%
“…The trans‐metallation reaction occurs via a chain shuttling agent (CSA). The resulting products, olefinic block copolymers (OBCs), are recently developed representatives of macromolecules with a complex, fine‐tuned microstructure composed of blocks of statistical copolymers with two different compositions, one being crystallizable and the other amorphous …”
Section: Introductionmentioning
confidence: 99%
“…The resulting products, olefinic block copolymers (OBCs), are recently developed representatives of macromolecules with a complex, fine-tuned microstructure composed of blocks of statistical copolymers with two different compositions, one being crystallizable and the other amorphous. [34] We previously reported on microstructural changes in the semibatch chain shuttling polymerization of ethylene and 1-octene using KMC simulation. [35][36][37][38] The KMC simulation was able to quantify many signature distributional characteristics of ethylene/1-octene copolymerization, such as the block composition, referred to as C8%, the block length represented by the number-average degree of polymerization DPn, the relative proportion of the blocks described via the hard block content (HB%), the number of linking points between blocks Macromol.…”
mentioning
confidence: 99%
“…They investigated the effect of CSA concentration on the system. Li et al studied the crystallization in polydisperse ethylene−octene multi‐block copolymers polymerized via chain‐shuttling chemistry. They concluded that the block lengths and the number of blocks per chain were characterized by most‐probable distributions.…”
Section: Introductionmentioning
confidence: 99%